Context Matters: Knowledge of baseline heart rate improves pediatric shock recognition. Issue 1 (March 2023) - Young, Riley; Papautsky, Elizabeth Lerner; Davies, Hobart; Tanem, Justinn; Scanlon, Matthew
This paper investigates the relationship between knowledge of baseline heart rate and shock recognition in pediatric patients. Through surveying attending physicians and advanced practice providers using a prospective survey tool, we demonstrate that providers are more likely to accurately identify shock when there is knowledge of the patient's baseline heart rate. These preliminary findings have the potential to inform changes to documentation and the electronic health record (EHR) to make this information more accessible, while also informing future studies aimed at improving clinical outcomes for these high-risk patients.